Validity of Electronic Device-Based Application for Visual Acuity Examination: A Systematic Review - Yulianti, Natasya F.; Munawir, Al; Adji, Novan K. (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2022)
Recent years, advances in the internet and communication technology have enabled the proliferation of digital medical devices with innovations in the form of health applications, including for visual acuity examination. However, the validity of these applications remains unclear. The limited mobility and health service during the COVID-19 pandemic underscores the urgent need to conduct research that validates these electronic device-based applications. Thus, this study aims to critically analyze whether the electronic device-based application is able to provide a valid and high-quality visual acuity examination. A systematic review was conducted through studies search on PubMed, MEDLINE, Springer, and Cochrane Library using specific keywords. After the studies were selected through inclusion and exclusion criteria, extraction was carried out. Publications from 2011 to the end of 2021 were reviewed, yielding in 1409 studies, of which 19 were included. The results showed a lower systematic bias for distance visual acuity testing with electronic device-based applications compared to standard reference tests with a mean difference of -0.08 to 0.10 logMAR. The validity of the near visual acuity examination with the application shows better results than the distance examination which is marked by smaller 95% limits of agreement range. The results of the analysis of Bland-Altman plots in all the studies reviewed showed that the accuracy of the examination results tended to increase in patients who had better visual acuity. In practice, the use of electronic device-based applications for visual acuity examination can increase the work effectiveness of medical personnel and the proliferation of digital medical devices. It can also be one of the breakthroughs in the field of remote medical services and support the implementation of telemedicine policies.